Cláusula penal: o valor da cominação e a redução equitativa da pena - Branco, Luiz Carlos (2010)
The penalty clause the value of the punishment and the equitable reduction of the penalty is linked to immemorial rights. That is, the penalty clause is a simple formula arising from Roman law. This formula establishes a social relationship based on legal standards that justify its compliance under all aspects, including philosophical aspects, as to the application of the right to the concrete case, in order to reach justice. And the value of the punishment and the equitable reduction of the penalty, expressly dealt with in the new Civil Code, are the parameters to dimension the value amount at each case. The purpose of this essay is to demonstrate that the value of the punishment and the equitable reduction of the penalty as a prerequisite for the application of the penalty clause will serve to measure the standard of value of the penalty in case of total or partial default, non-execution of some special clause or delay. The standard of value of the penalty is under the responsibility of our courts in pursuit of a legal democratic state, a state that guarantees the fundamental rights of the human being. The study of this topic is justified by the attempt to settle visible conflicts among principles that guarantee fundamental rights. This is entitled theory of the weighing of goods and values. This essay is of topical interest since this is a concrete issue in several countries that have a similar legal structure. As from 2002, the Brazilian system established that the equitable reduction of the penalty is mandatory. Before 2002, this reduction was a judge‟s prerogative. The methods used in this research were basically the deductive and inductive methods under a dialectic perspective. The results obtained were the following: 1) a judgment will be fair if the application of the law to the concrete case was correct. And it will be correct the application of the law that took into consideration the real or substantial equality of the parties - to treat equal persons equally and to treat unequal persons unequally in the exact measure of their inequality; 2) this is reached through the application of the adequate value of punishment; and 3) as to the equitable reduction of the penalty, it became mandatory at the time of its application. In the past, this reduction was a judge‟s prerogative that many times did not exercise it